2022
DOI: 10.1002/jbm.b.35105
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancement in polymer/halloysite nanotube nanocomposites for biomedical applications

Abstract: Halloysite nanotubes (HNTs) have recently been the subject of extensive research as a reinforcing filler. HNT is a natural nanoclay, non‐toxic and biocompatible, hence, applicable in biomedical fields. This review focuses on the mechanical, thermal, and functional properties of polymer nanocomposites with HNT as a reinforcing agent from an experimental and theoretical perspective. In addition, this review also highlights the recent applications of polymer/HNT nanocomposites in the biomedical fields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 189 publications
0
6
0
Order By: Relevance
“…This combination resulted in superior mechanical and functional properties, due to synergetic effects that also enhanced the interactions with biological species [ 242 ]. Regarding the addition of ceramic nanotubes, there is a recent trend of incorporating naturally occurring hollow nanotubes as a reinforcing agent in polymer composites, significantly improving mechanical properties such as stiffness and flexibility while maintaining good cytocompatibility and cell adhesion [ 245 , 246 ]. Among them, halloysite nanotubes (HNTs) are the most commonly reported ceramic nanotubes for this purpose, along with carbon nanotubes (CNTs), but these ones will be commented on later.…”
Section: Hybrid Hydrogel Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…This combination resulted in superior mechanical and functional properties, due to synergetic effects that also enhanced the interactions with biological species [ 242 ]. Regarding the addition of ceramic nanotubes, there is a recent trend of incorporating naturally occurring hollow nanotubes as a reinforcing agent in polymer composites, significantly improving mechanical properties such as stiffness and flexibility while maintaining good cytocompatibility and cell adhesion [ 245 , 246 ]. Among them, halloysite nanotubes (HNTs) are the most commonly reported ceramic nanotubes for this purpose, along with carbon nanotubes (CNTs), but these ones will be commented on later.…”
Section: Hybrid Hydrogel Compositesmentioning
confidence: 99%
“…The main reason is that HNTs are composed of hydrous aluminosilicate with a native tubular structure that can be easily obtained from natural resources. Along with its biocompatibility with human body, HNTs has been proposed as an interesting, valuable and low-cost alternative for bone tissue engineering applications [ 245 , 247 ]. Huang et al (2019) reported the successful incorporation of HNTs into a GelMA hydrogel by photopolymerization process and that HNTs addition increased the mechanical performance and the capability to support cell adhesion and proliferation of human dental pulp stem cells [ 246 ].…”
Section: Hybrid Hydrogel Compositesmentioning
confidence: 99%
“…Nanotubes are composed of organic or inorganic atoms and can form single‐ or multi‐walled tubes with considerable internal volume. [ 149–151 ] Due to their extensive internal surface area and high aspect ratio, [ 152–154 ] carbon nanotubes (CNTs) with proper mechanical properties and biocompatibility are often used to prepare 3D‐printed functionalized bioscaffolds to enhance the scaffolds' mechanical properties and avoid mechanical damage due to fragility during use on. Liu et al.…”
Section: Incorporation Of Nanomaterials Into 3d‐printed Productsmentioning
confidence: 99%
“…[7][8][9] Besides MWCNTs, halloysite nanotubes (HNTs) have also been used as materials for biomedical purposes, such as drug delivery, 10 disease therapy, 11 and tissue scaffolds. 12 Although HNTs have been considered as relatively biocompatible NMs for biomedical uses, 13,14 their potential toxicity should still be carefully evaluated.…”
mentioning
confidence: 99%
“…19,20 For HNTs, they are derived from natural clay mineral and have been considered to be highly biocompatible. 13,14 However, recent studies still reported that repeated exposure to HNTs induced injury to mouse lungs 21 and livers 22 in vivo. We reported recently that intravenous exposure to HNTs impaired NO signaling pathways in mouse aortas, although the effect of HNTs was weaker than MWCNTs.…”
mentioning
confidence: 99%